European space cooling demands. (1st September 2016) - Werner, Sven
Abstract: Information about European space cooling demands is rare, since cooling demands are not properly measured, when electricity is used for operating space cooling devices. Cooling demands are only measured at deliveries from district cooling systems. However, information about cooling demands by location and country is required for planning district cooling systems and modelling national energy systems. In order to solve this cooling information dilemma, space cooling demands have been assessed for European service sector buildings. These estimations were based on cold deliveries from twenty different European district cooling locations in eight countries. Main findings are that (1) the estimated specific cold deliveries are somewhat lower than other estimations based on electricity inputs and assumed performance ratios, (2) aggregated space cooling demands are presented by country, and (3) an European contour map is presented for average specific space cooling demands for service sector buildings. Highlights: Low availability of data on European space cooling demands. District cooling deliveries are proportional to European Cooling Indices. European space cooling demands estimated from measured cooling deliveries. European map provided for specific space cooling demands in service sector. Aggregated space cooling demands are somewhat lower than other estimations.